Characterization of two novel chemolithoautotrophic bacteria of Sulfurovum from marine coastal environments and further comparative genomic analyses revealed species differentiation among deep-sea hydrothermal vent and non-vent origins - Wang, Jun; Zheng, Qiang; Wang, Shasha; Zeng, Jialing; Yuan, Qing; Zhong, Yangsheng; Jiang, Lijing; Shao, Zongze (Frontiers in Marine Science, 2023)
Bacteria of the genus Sulfurovum within the class Campylobacteria are widespread in global oceans and are predominant in sulfide-rich environments. However, little is known about their adaptation to such harsh environments owing to their resistance to cultivation. In this study, we obtained three pure cultures of this genus from marine coastal environments and compared them with those obtained from the deep sea. Phylogenetic analysis of 16S rRNA gene sequences indicated that they represent two novel species of the genus, sharing 95.9%-96.1% sequence similarity to Sulfurovum aggregans Monchim33 T . Based on the multiphase classification results, the type strains XTW-4 T and zt1-1 T were proposed to represent two new species: Sulfurovum xiamenensis sp. nov. and Sulfurovum zhangzhouensis sp. nov., respectively. These coastal isolates were also obligate chemoautotrophs featuring molecular hydrogen as an electron donor and molecular oxygen, thiosulfate, or elemental sulfur as the sole electron acceptor. Comparative genomic analyses based on 11 Sulfurovum species further revealed a clear differentiation between hydrothermal vent and non-vent origins. The non-vent Sulfurovum can use thiosulfate as an electron acceptor but lacks denitrification pathways, whereas the vent bacteria can respire nitrate through complete denitrification pathways. Moreover, the non-vent Sulfurovum contained a nitrogen fixation pathway, implying their adaptation to nitrogen source-deficit niches. In addition, non-vent Sulfurovum species adapted to a higher oxygen concentration via multiple antioxidative defense mechanisms. These phenotypic and genotypic features help us to understand the ecological role of Sulfurovum bacteria in marine ecosystems.